Enhancement in fatigue life of NiTi shape memory alloy thermal actuator wire. (1st January 2016) - Saikrishna, C.N.; Ramaiah, K.V.; Paul, D.; Bhaumik, S.K.
Abstract: The effect of intermittent overload cycles (OLCs) on the fatigue life of NiTi wires has been investigated. The results showed that the OLCs were effective in enhancing the fatigue life of the NiTi wires undergoing thermo-mechanical cycling (TMC). Three distinct regions were identified in the No. of cycles to failure vs. over load ratio (OLR) plot. Region I (OLR ≤ 1.5) corresponded to threshold OLR, at and below which the OLCs did not have any effect on the fatigue behaviour of the NiTi wires. In region II (1.5 < OLR < 2.5) the fatigue life was found to increase monotonically with the increase in OLR. In region III (OLR ≥ 2.5), the increase in fatigue life was quite substantial. The actuator wire with OLCs of OLR 2.5 showed fatigue life of 3 times of that of the wire with OLR of 2.25 and 9 times of that without OLCs. Study revealed that the effect of OLCs towards enhancement in fatigue life was cumulative, and its withdrawal at any stage during the TMC resulted in a life lower than that of the wire subjected to OLCs till fracture. The presence of stabilized martensite phase in the microstructure was found beneficial towards enhancement in fatigue life and its restoration by healing treatment had a detrimental effect on the life of the actuator wires. Graphical abstract: